2011
DOI: 10.2337/dc11-0135
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus in Relation to Maternal Dietary Heme Iron and Nonheme Iron Intake

Abstract: OBJECTIVEHigher heme iron intake is associated with increased type 2 diabetes risk. However, no previous study has evaluated gestational diabetes mellitus (GDM) risk in relation to heme iron intake during pregnancy. We investigated associations of maternal preconceptional and early pregnancy heme and nonheme iron intake with subsequent GDM risk.RESEARCH DESIGN AND METHODSWe conducted a prospective cohort study of 3,158 pregnant women. A food frequency questionnaire was used to assess maternal diet. Multivariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 20 publications
(41 reference statements)
8
92
1
4
Order By: Relevance
“…Moreover, current evidence is dominated by findings from the Nurses' Health Study II and should be interpreted with caution because incomplete adjustment or clustering of health behaviors may have confounded the reported associations. In terms of nutrients, higher intake of total fat, cholesterol, and heme iron were associated with higher GDM risk (15)(16)(17)23,24). In terms of foods, higher consumption of red meat, processed meat, and eggs was associated with a higher risk of GDM (15,25,26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, current evidence is dominated by findings from the Nurses' Health Study II and should be interpreted with caution because incomplete adjustment or clustering of health behaviors may have confounded the reported associations. In terms of nutrients, higher intake of total fat, cholesterol, and heme iron were associated with higher GDM risk (15)(16)(17)23,24). In terms of foods, higher consumption of red meat, processed meat, and eggs was associated with a higher risk of GDM (15,25,26).…”
Section: Discussionmentioning
confidence: 98%
“…Two prospective cohort studies examining intake of heme iron before (23) and during pregnancy (24) showed an increased risk of GDM with higher intake (Supplementary Table 1). (24).…”
Section: Heme Ironmentioning
confidence: 99%
“…A consensus statement published in 2007 (147) advised that pregnant and lactating women's intake of DHA should be at least 200 mg/d. This is in line with the FAO (13), which set the average nutrient requirement (ANR) to 200 mg/d.…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
“…The results on allergic diseases and cognition differ somewhat between the effects of fish oil and other PUFA supplementation (149,150). An intake of DHA slightly greater than 1 g/d or a total intake of 2.7 g/d of n-3 LCPUFA (both EPA and DHA) is considered safe (147).…”
Section: Pregnancy and Lactationmentioning
confidence: 99%
“…Por otro lado, en un estudio prospectivo de cohorte de 3.158 mujeres se encontró que altos niveles de ingesta de hierro hemo dietético preconcepcional podían estar asociados con un mayor riesgo de padecer diabetes gestacional 46 , pero en este caso cabría analizar también si los niveles elevados de hierro hemo están ligados a un alto consumo de carnes, vinculado a su vez a un patrón de alimentación menos "saludable" y con menor variabilidad de vitaminas y minerales, el cual se correspondería con el que se describe como "patrón occidental" (rico en carnes, alimentos precocinados y bajo en frutas). Dicho patrón se asoció con menor cantidad de folato en eritrocitos, bajos niveles de vitamina B 6 y concentraciones de homocisteína elevada 15 , por lo que no sería el perfil de dieta apropiado para mujeres en edad fértil.…”
Section: Hierrounclassified